2015
DOI: 10.3892/or.2015.4396
|View full text |Cite
|
Sign up to set email alerts
|

PBOV1 correlates with progression of ovarian cancer and inhibits proliferation of ovarian cancer cells

Abstract: Prostate and breast cancer overexpressed 1 (PBOV1) is significantly upregulated in prostate, breast and bladder cancer, while its expression status in ovarian cancer and its clinical significance are unclear. We examined the expression levels of PBOV1 mRNA and protein in ovarian cancer cell lines and primary tissues using real-time PCR and western blotting. Immunohistochemistry was employed to analyze PBOV1 expression in 17 normal ovaries, 13 cystadenoma tissues, 14 borderline tumor tissues, and 165 clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(31 reference statements)
0
13
1
Order By: Relevance
“…A possible role for PBOV1 as an immune-modulating protein that enhances survival outcomes in ovarian cancers has been proposed based on its higher mRNA and protein expression in early stage tumors (stage I-II) compared to higher staged tumors (III-IV). 16 Our results in PCa samples from radical prostatectomy failed to reveal high protein levels in lower grade tumors. However, outcome data on our patient groups were unavailable, and thus we could not determine whether PBOV1 protein expression levels impact overall or long-term survival.…”
Section: Review Of Our Findings With Recent Publicationscontrasting
confidence: 53%
See 3 more Smart Citations
“…A possible role for PBOV1 as an immune-modulating protein that enhances survival outcomes in ovarian cancers has been proposed based on its higher mRNA and protein expression in early stage tumors (stage I-II) compared to higher staged tumors (III-IV). 16 Our results in PCa samples from radical prostatectomy failed to reveal high protein levels in lower grade tumors. However, outcome data on our patient groups were unavailable, and thus we could not determine whether PBOV1 protein expression levels impact overall or long-term survival.…”
Section: Review Of Our Findings With Recent Publicationscontrasting
confidence: 53%
“…A possible role for PBOV1 as an immune‐modulating protein that enhances survival outcomes in ovarian cancers has been proposed based on its higher mRNA and protein expression in early stage tumors (stage I–II) compared to higher staged tumors (III–IV) . Our results in PCa samples from radical prostatectomy failed to reveal high protein levels in lower grade tumors.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It was also identified that the expression of PBOV1 in prostate cancer cells is upregulated by dihydrotestosterone (12). In addition, PBOV1 transcription in breast cancer cells was demonstrated to be downregulated by estradiol in a dose-dependent manner (13), and the mRNA and protein expression of PBOV1 was identified to be upregulated in ovarian cancer cell lines (14). However, there were negative associations between high PBOV1 expression and ascending histological grade and late TNM stage (14).…”
Section: Introductionmentioning
confidence: 99%